Scope and challenges of robotic surgery: a trainee’s perspective - Maturi, Ramesh; Rao, Someswara (International Surgery Journal, 2025)
Background: Robotic surgical technology is here to stay and training on the platform is a necessity for all surgeons. It is an advancement over laparoscopy as a minimally invasive technique. It overcomes many challenges associated with laparoscopy while simplifying the learning process of minimally invasive surgery. Methods: It is a prospective observational study of patients who presented to the administrative unit within the Department of Surgical Oncology, MNJ institute of oncology and regional cancer center and planned for robotic surgical procedure Results: A total of 59 cases have been performed in a single administrative unit of Department of Surgical Oncology, MNJ institute of oncology and Regional Cancer Center from September 2023 to January 2025 over a period of 17 months of which 61 % (n=36) were females and 39% (n=23) were males. The age range of operated patients was 23- 72 years. 51-60 years was the most common age group 28.8% (n=17). Colorectal surgeries and gynecological surgeries share 42.3% each (n=25). The most common surgery performed was robotic radical hysterectomy 40.6% (n=24) which mimics patient load patterns of the department. Conclusions: Learning skill sets over the robotic platform is facilitated by the prior learnings in executing laparoscopic surgery. The authors do not agree to popular misconception that one needs to unlearn certain skills from laparoscopic surgery to transform into robotic surgeons and infact, they believe prior laparoscopic experience is a favorable qualification.